Applications of Electrospinning for Tissue Engineering in Otolaryngology. (April 2021) - Heilingoetter, Ashley; Smith, Sharon; Malhotra, Prashant; Johnson, Jed; Chiang, Tendy
Objective: In tissue engineering, biomaterials create a 3D scaffold for cell-to-cell adhesion, proliferation and tissue formation. Because of their similarity to extracellular matrix and architectural adaptability, nanofibers are of particular interest in tissue engineering. Electrospinning is a well-documented technique for nanofiber production for tissue engineering scaffolds. Here we present literature on the applications of electrospinning in the field of otolaryngology. Review Methods: A PubMed database search was performed to isolate articles published about applications of electrospun nanofibers for tissue engineering in otolaryngology. Study design, size, material tested, site of application within the head and neck, and outcomes were obtained for each study. Results: Almost all data on electrospinning in otolaryngology was published in the last 6 years (84%), highlighting its novelty. A total of 25 pre-clinical studies were identified: 9 in vitro studies, 5 in vivo animal studies, and 11 combination studies. Sites of application included: tracheal reconstruction (n = 16), tympanic membrane repair (n = 3), cranial nerve regeneration (n = 3), mastoid osteogenesis (n = 1) and ear/nose chondrogenesis (n = 2). Implications for Practice: Tissue engineering is a burgeoning field, with recent innovative applications in the field of otolaryngology. Electrospun nanofibers specifically have relevant applications in the field of otolaryngology, due in part to their similarity to native extracellular matrix, with emerging areas of interest being tympanic membrane repair, cranial nerve regeneration and tracheal reconstruction.